1993
DOI: 10.1007/bf01658699
|View full text |Cite
|
Sign up to set email alerts
|

Malrotation of the intestine

Abstract: Malrotation of the intestinal tract is a product of a well defined aberrant embryology. Because the consequences of malrotation associated with a midgut volvulus may be catastrophic, an understanding of the anatomy, diagnostic criteria, and appropriate therapy for this putative emergency illness is imperative. This report summarizes a recent 18-month experience with this diagnosis and contrasts this experience with that in the published literature. More than half (14/22) of the patients presented during the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
217
0
16

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(237 citation statements)
references
References 33 publications
4
217
0
16
Order By: Relevance
“…Disturbance of this process will lead to incomplete or non-rotation of the foetal midgut. This condition affects approximately 1 in 500 live births with the vast majority of the associated complications presenting in the first month of life when its diagnosis is made [1][2][3] . It has been reported that well over 90% of the affected individuals manifest by the time of their first birthday [1][2][3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disturbance of this process will lead to incomplete or non-rotation of the foetal midgut. This condition affects approximately 1 in 500 live births with the vast majority of the associated complications presenting in the first month of life when its diagnosis is made [1][2][3] . It has been reported that well over 90% of the affected individuals manifest by the time of their first birthday [1][2][3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…This condition affects approximately 1 in 500 live births with the vast majority of the associated complications presenting in the first month of life when its diagnosis is made [1][2][3] . It has been reported that well over 90% of the affected individuals manifest by the time of their first birthday [1][2][3][4][5] . The diagnosis of midgut malrotation is rarely reported in adults [2,[4][5][6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…This condition most commonly presents during the first year of life and has high rates of morbidity and mortality [1,2] . Midgut volvulus without malrotation is an extremely rare surgical condition, which may also occur during gestation [3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…In another study performed in 2008 in America, although high sensitivity of GI series evaluation was confirmed in the detection of intestinal malrotation, this method did not have proper specificity and diagnostic value (18). In a study performed by Torres et al 95% sensitivity and 86% specificity was reported for upper GI series in malrotation diagnosis (19). Table 3 shows sensitivity and specificity of upper GI series and ultrasound in some studies.…”
Section: Discussionmentioning
confidence: 98%